Melatonin in different food samples: Recent update on distribution, bioactivities, pretreatment and analysis techniques. (January 2023) - Zhang, Xin-yue; Zhang, Yuan; Zhou, Yu; Liu, Zhi-fei; Wei, Bin-bin; Feng, Xue-song
Graphical abstract: Highlights: Summarizing the distribution, content, bioactivities and health potential of MLT. Comprehensively reviewing the pretreatment and analysis techniques of MLT. Introducing new materials and solvents used in different pretreatment techniques. Exploring the characteristics, application and the latest progress of the analysis methods for MLT. Exploring future development tendency of the pretreatment and analysis methods for MLT. Abstract: Melatonin (MLT) plays a significant role on maintaining the basic physiological functions and regulating various metabolic processes in plentiful organisms. Recent years have witnessed an increase in MLT's share in global market with its affluent functions. However, the worrisome quality issues and inappropriate or excessive application of MLT take place inevitably. In addition, its photosensitive properties, oxidation, complex substrate concentration and trace levels leave exact detection of MLT doubly difficult. Therefore, it is essential to exploit precise, sensitive and stable extraction and detection methods to resolve above questions. In this study, we reviewed the distribution and bioactivities of MLT and conducted a comprehensive overview of the developments of pretreatment and analysis methods for MLT in food samples since 2010. Commonly used pretreatment methods for MLT include not only traditional techniques, but also novel ones, such as solid-phase extraction, QuEChERS, microextraction by packed sorbent, solid phase microextraction, liquid phase microextraction, and so on. Analysis methods include liquid chromatography coupled with different detectors, GC methods, capillary electrophoresis, sensors, and so on. The advantages and disadvantages of different techniques have been compared and the development tendency was prospected.